A response surface methodology study on the effects of some phenolics and storage period length on vegetable oil quality: change in oxidation stability parameters - Karaman, Safa; Toker, Omer Said; Ozturk, Ismet; Yalcin, Hasan; Kayacier, Ahmed; Dogan, Mahmut; Sagdic, Osman (Tubitak Scientific & Technological Research Council Turkey, 2014)
In the present study, response surface methodology was conducted for the determination of effects of some phenolics (gallic acid, ellagic acid, and quercetin) on some stability parameters of mixed oil prepared with sunflower and hazelnut oils (50:50, v/v). In this respect, peroxide value (PV), free fatty acids (FFAs), p-anisidine value, induction period, and refractive index of mixed oil were investigated. Predictive regression equations were constructed for the estimation of each studied parameter (R-2 > 0.861). The storage period caused a significant increase in the peroxide value, FFAs, p-anisidine, and refractive index values of the mixed oil, while it decreased the induction period value of oil (P < 0.01). The addition of gallic acid significantly retarded oxidation (P < 0.05), and in general gallic acid and quercetin were found to be effective for preserving oil against oxidation.
Keywords: Vegetable oil; phenolics; storage; oxidation; response surface methodology; ANTIOXIDANT ACTIVITY; SUNFLOWER OIL; SOYBEAN OIL; EXTRACTS; POTATO; KINETICS; OXYGEN; ACID; PEEL; Agriculture; Forestry